Kekuatan Artificial Intelligence Tiongkok dan Kekhawatiran Masyarakat Global: Resensi Buku - Arief Bakhtiar Darmawan (Universitas Diponegoro, 2020)
This paper reviews a new book written by Kai-Fu Lee titled AI Superpowers: China, Silicon Valley, and the New World Order which address the question of how artificial intelligence reshape the world order and how its impact on the world economy.